1966 - Tollison, Robert D. (Public choice, 2012)
I first encountered The Calculus of Consent in September 1966 as a first-year graduate student at the University of Virginia. I chose Virginia because it was the first school to which I applied that offered me a fellowship. I could have equally gone to North Carolina or Duke had I waited. I literally knew very little about the work that was being done by the faculty at these schools. Little did I realize at the time that I had made a fortuitous choice. In 1966 both of the authors of the Calculus were in residence in Charlottesville as members of the Economics Department. The book was not formally assigned as a reading in any of my classes, but it was a commonly and much discussed topic among the graduate students. The book did not have an immediate effect on my work or me. It was more like osmosis, whereby gradually over time ideas and thoughts gel and insights develop. Looking back, however, I can see that the path I have taken is directly related to the early influence of the Calculus. Early reviews and critiques of the book stressed the need to follow a work of pure theory with empirical testing. This was an idea that captured my imagination, and so in the mid-1970s, I began my work in empirical public choice. The idea was simply to find testable implications in public choice theory and to confront them with data. With the help of co-workers I think that I can fairly claim a modicum of success in this enterprise. Topics on which I (we) have reported empirical findings include: legislator pay, interest groups, term limits, campaign spending, redistricting, voting behavior, public spending, taxes, deficits, bureaucracy, regulation, bicameralism, and still others. Had I gone to another graduate program, no doubt none of this work would have been done. So I would say that the Calculus had a big impact on my work, as did the luck (serendipity) of going to a graduate program that was unique, vital, and competitive, with really fine students. Charlottesville and Buchanan and Tullock opened my eyes to a world of possibilities that turned into a life of scholarship, good times, and enjoyable colleagues and students. I do not know what the road not taken (opportunity cost) would have been like, but I cannot imagine anything better than the one I did take. In fact, I probably otherwise would have ended up teaching four courses a semester at a small college. Adapted from the source document.